2021
DOI: 10.1177/0170840621994521
|View full text |Cite
|
Sign up to set email alerts
|

Investments in Nascent Project-Based Enterprises: The interplay between role-congruent reputations and institutional endorsement

Abstract: We study nascent project-based enterprises (PBEs) through the lens of upper echelons and institutional theory. We analyse the interplay between the different role-congruent reputations of their project entrepreneurs and the institutional endorsement of their project idea, theorizing how these affect PBEs’ ability to attract private investments. In the context of the Italian film industry, we find that the commercial reputation of the project entrepreneur in the producer role is crucial for attracting investors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 113 publications
(261 reference statements)
0
3
0
Order By: Relevance
“…However, the direction of change is determined by lower-echelon bureaucrats with low formal power, and by bureaucracy’s core principles. Moreover, our research provides insights into the interplay between agency and structure (Tomaselli, Ebbers, & Torluccio, 2022) by outlining the two sources of legitimacy that elevate the new rules, roles and processes designed by the project teams to an adapted form of bureaucracy: the actions of bureaucratic senior officials (agency) and the legitimacy derived from bureaucratic rule-bound processes (structure).…”
Section: Discussionmentioning
confidence: 99%
“…However, the direction of change is determined by lower-echelon bureaucrats with low formal power, and by bureaucracy’s core principles. Moreover, our research provides insights into the interplay between agency and structure (Tomaselli, Ebbers, & Torluccio, 2022) by outlining the two sources of legitimacy that elevate the new rules, roles and processes designed by the project teams to an adapted form of bureaucracy: the actions of bureaucratic senior officials (agency) and the legitimacy derived from bureaucratic rule-bound processes (structure).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of client ties, new project-entrepreneurs typically lack these during nascence (Stinchcombe, 1965). In a study of another key tie, Tomaselli, Ebbers and Torluccio (2021) indicated that during nascence, project-entrepreneurs’ commercial and artistic reputations enhance prospects of tie formation with investors. Nevertheless, it is little understood how without these attributes ties with these key resource holders are established.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Broadly speaking, predicting and managing the novelty of project outcomes is a complicated task as several facets of creative projects unfold gradually, in unique ways that were not always originally intended (Caves, 2003). The overall ambiguity about processes that lead to producing novel outcomes, combined with exceptional degrees of freedom that creative decision-makers demand for crafting unique outcomes make the creative processes difficult to monitor (Tomaselli, Ebbers, & Torluccio, 2021). Especially in project-based contexts that rely on network organization (Powell, 1990), the unique composition of each project in terms of the intended outcome and participating collaborators strictly limits the basis for predicting individuals' creativity.…”
Section: Network Evolution and Creative Influencementioning
confidence: 99%